1990
DOI: 10.1128/aem.56.3.681-685.1990
|View full text |Cite
|
Sign up to set email alerts
|

Influence of transition metals added during sporulation on heat resistance of Clostridium botulinum 113B spores

Abstract: Sporulation of Clostridium botulinum 113B in a complex medium supplemented with certain transition metals (Fe, Mn, Cu, or Zn) at 0.01 to 1.0 mM gave spores that were increased two to sevenfold in their contents of the added metals. The contents of calcium, magnesium, and other metals in the purified spores were relatively unchanged. Inclusion of sodium citrate (3 g/liter) in the medium enhanced metal accumulation and gave consistency in the transition metal contents of independent spore crops. In citrate-suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…The Fe" content was relatively low even in Fe-supplemented spores themselves and, instead, Ca" was a major constituent. These findings concur with previous results of other researchers (Kihm et al, 1990 ;Marquis and Shin, 1994) . As compared with that in the spores of strain 168, the Mn" content in Mn-supplemented spores of strain ATCC9372 was relatively low.…”
Section: Divalent Cation Contents Of Sporessupporting
confidence: 94%
See 1 more Smart Citation
“…The Fe" content was relatively low even in Fe-supplemented spores themselves and, instead, Ca" was a major constituent. These findings concur with previous results of other researchers (Kihm et al, 1990 ;Marquis and Shin, 1994) . As compared with that in the spores of strain 168, the Mn" content in Mn-supplemented spores of strain ATCC9372 was relatively low.…”
Section: Divalent Cation Contents Of Sporessupporting
confidence: 94%
“…It remains unclear why and how the mineralization affects the spore resistance in the solution phase and in the vapor phase differently. One possible factor may be a specifi scavenging action of intrasporal Mn2+ against hydroxyl radicals generated from hydrogen peroxide (Kihm et al, 1990). This action of Mn2+ might be marked in dehydrated spores rather than hydrated spores.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed effect of SSS on sporulation and toxigenicity of C. botulinum spores was not reported in previous studies. Kihm et al (1990) found that C. botulinum 113B sporulated well in media containing 0.01 to 1.0 mM Fe, Cu, Mn, or Zn.…”
Section: Spore Productionmentioning
confidence: 97%